Doxycycline Induces Apoptosis of Brucella Suis S2 Strain-Infected HMC3 Microglial Cells by Activating Calreticulin-Dependent JNK/p53 Signaling Pathway - Wang, Zhao; Wang, Yanbai; Yang, Huan; Guo, Jiayu; Wang, Zhenhai (Frontiers in Cellular and Infection Microbiology, 2021)
Neurobrucellosis is a chronic complication of human brucellosis that is caused by the presence of Brucella spp in the central nervous system (CNS) and the inflammation play a key role on the pathogenesis. Doxycycline (Dox) is a widely used antibiotic that induces apoptosis of bacteria-infected cells. However, the mechanisms of Brucella inhibition of microglial apoptosis and Dox induction of apoptosis are still poorly understood. In this study, we found that Brucella suis S2 strain (B. suis S2) increased calreticulin (CALR) protein levels and inhibited HMC3 cell apoptosis. Hence, we constructed two HMC3 cell line variants, one with stable overexpression (HMC3-CALR) and one with low expression of CALR (HMC3-sh-CALR). CALR was found to decrease levels of p-JNK and p-p53 proteins, as well as suppress apoptosis in HMC3 cells. These findings suggest that CALR suppresses apoptosis by inhibiting the JNK/p53 signaling pathway. Next, we treated HMC3, HMC3-CALR and HMC3-sh-CALR cell lines with B. suis S2 or Dox. Our results demonstrate that B. suis S2 restrains the JNK/p53 signaling pathway to inhibit HMC3 cell apoptosis via increasing CALR protein expression, while Dox plays the opposite role. Finally, we treated B. suis S2-infected HMC3 cells with Dox. Our results confirm that Dox induces JNK/p53-dependent apoptosis in B. suis S2-infected HMC3 cells through inhibition of CALR protein expression. Taken together, these results reveal that CALR and the JNK/p53 signaling pathway may serve as novel therapeutic targets for treatment of neurobrucellosis.